Cost and Return Analysis of Durian Cultivation in Mueang Prachinburi District, Prachinburi Province - sanma, wasana; Apisitpinyo, Benjamas (Journal of Management Science Nakhonratchasima University, 2025)
This research aimed to 1) examine the production costs of durian cultivation, 2) analyze the returns from durian cultivation, and 3) evaluate the financial feasibility of durian cultivation. The sample consisted of 35 farmers in Mueang Prachinburi District, Prachinburi Province, who had cultivated Monthong durian for at least three years and maintained cost–revenue records. Purposive sampling was employed, and data were collected through structured questionnaires and in-depth interviews. The analysis utilized percentage statistics, direct and total cost calculations, and financial feasibility indicators, including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Return on Investment (ROI), and Profitability Index (PI). The findings revealed that 1) the total production cost from land preparation to harvest averaged 195,283.33 baht, 2) the return on investment (ROI) ranged from 23.13% to 152.06%, with smaller production areas exhibiting substantially higher returns, while larger areas faced greater management burdens and lower per-rai efficiency; and 3) all area groups demonstrated financial viability, with IRR, ARR, NPV, PI, and payback periods falling within acceptable ranges. Small- to medium-sized farms achieved the highest returns and the shortest payback periods. In contrast, larger farms remained financially viable but required more extended payback periods due to higher management burdens.